One pot preparation of α-dithioacetal/α-diselenoacetal amides via a dual-C–S/C–Se bond formation and C–C bond cleavage cascade of 3-oxo-butanamides12. Issue 15 (27th June 2018) - Zou, Jiao-xia; Wang, Yong-qiang; Huang, Long-tao; Jiang, Yi; Chen, Jin-hong; Zhu, Long-qing; Yang, Yu-hang; Feng, Yi-yue; Peng, Xue; Wang, Zhen
Abstract : A new and practical approach to α-dithioacetal/α-diselenoacetal amides has been developed. Abstract : A new and practical approach to α-dithioacetal/α-diselenoacetal amides has been developed, combining sequential functionalization of amides and a C–C bond cleavage strategy. In this reaction, various α-dithioacetal/α-diselenoacetal amides from 3-oxo-butanamides were prepared in one step with good regioselectivity and functional group tolerance.